The Manifestation of Cultural Identity and Transculturation in D.H. Lawrence’s Mornings in Mexico - Soumitra Mukherjee (PostScriptum: An Interdisciplinary Journal of Literary Studies, 2019)
This paper deals with the issues of cultural identity and transcultural spaces in the travel writing of D. H. Lawrence. The travel writings of Lawrence are important analyses of modern culture. They definitely give opportunity to study the role of cultural identity in the genre of travel writing. Travel writing as a genre primarily deals with the experiences of a travel writer travelling to different unknown cultures or places and most of the travel writings of Lawrence document the meeting of two alien cultures. The strange meetings represented by the travel writer’s own culture and the culture of the people of the country travelled by him make a transcultural space. The strangeness produced out of the encounter of two different cultures is the most important issue here. The strangeness between the self and the world brings with it the issues of ‘cultural identity’ and ‘transculturation’. Lawrence’s Mexican travel writing, Mornings in Mexico (1927) is built on the notion of cultural identity. His encounter with the Mexicans reminds of the vast gulf of difference between his European culture and the native Mexican culture. As transculturation is a transition from one culture to another, Lawrence’s encounter with the Mexican culture definitely produces a transcultural space that is only translated through the strangeness existing between the two cultures.